2016
DOI: 10.4049/jimmunol.1600282
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Adjuvant Synergy: Dual TLR7/8 and Mincle Activation of Human Newborn Dendritic Cells Enables Th1 Polarization

Abstract: Due to functionally distinct cell-mediated immunity, newborns and infants are highly susceptible to infection with intracellular pathogens. Indeed, neonatal Ag-presenting dendritic cells (DCs) demonstrate impaired Th1 responses to many candidate adjuvants, including most TLR agonists (TLRAs). Combination adjuvantation systems may provide enhanced immune activation but have typically been developed without regard to the age of the target population. We posited that distinct combinations of TLRAs and C-type lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 60 publications
3
90
0
Order By: Relevance
“…Mechanisms that lead to this early life pattern of innate cytokine response include (1) high mononuclear cell levels of intracellular cyclic adenosine monophosphate (cAMP), a secondary messenger that suppresses Th1 but enhances Th2 and anti-inflammatory cytokine production (Levy et al, 2006) and (2) altered DNA binding capacity of transcription factors such as IRF3 to the promoter regions of cytokine genes secondary to age-specific chromatin remodelling (Lissner et al, 2015). Of note, simultaneous stimulation of TLR and C-type lectin receptors (CLR) reveals marked synergy in immune activation as compared to single PRR stimulation, a synergy that strongly varies with age (Lemoine et al, 2015;van Haren et al, 2016a). Specifically, coactivation of newborn DCs via the CLR agonist Dectin or macrophage-inducible C-type lectin (Mincle), and TLR7/8 potently drives caspase-1 and NF-kB activation and Th1-supporting cytokine production (including IL-12p70, overcoming the agespecific epigenetic hurdle in early life for IRF3 function) that results in autologous T cell polarization toward a Th-1 phenotype.…”
Section: Innate Immunity Integrates Environmental Signals and Providementioning
confidence: 99%
“…Mechanisms that lead to this early life pattern of innate cytokine response include (1) high mononuclear cell levels of intracellular cyclic adenosine monophosphate (cAMP), a secondary messenger that suppresses Th1 but enhances Th2 and anti-inflammatory cytokine production (Levy et al, 2006) and (2) altered DNA binding capacity of transcription factors such as IRF3 to the promoter regions of cytokine genes secondary to age-specific chromatin remodelling (Lissner et al, 2015). Of note, simultaneous stimulation of TLR and C-type lectin receptors (CLR) reveals marked synergy in immune activation as compared to single PRR stimulation, a synergy that strongly varies with age (Lemoine et al, 2015;van Haren et al, 2016a). Specifically, coactivation of newborn DCs via the CLR agonist Dectin or macrophage-inducible C-type lectin (Mincle), and TLR7/8 potently drives caspase-1 and NF-kB activation and Th1-supporting cytokine production (including IL-12p70, overcoming the agespecific epigenetic hurdle in early life for IRF3 function) that results in autologous T cell polarization toward a Th-1 phenotype.…”
Section: Innate Immunity Integrates Environmental Signals and Providementioning
confidence: 99%
“…induced immune responses observed in neonates and elderly [66,67]. The potential to overcome the impaired immunity of specific age or immunocompromised risk groups is therefore also an important application for future studies of the adjuvant combination developed in the present study.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…Whilst no vaccines including TLR7/8 ligands are yet licensed, studies in monkeys have shown that including a TLR7/8 agonist allows for boosting of anti-HIV Envelope IgG responses compared to when alum was used alone [64,65]. Furthermore, the capability of co-adjuvantation with TLR7 agonists to redirect the alum-induced T cell responses towards IFN-ɣ producing Th1 cells was also demonstrated in monkeys [67]. It was recently found that a TLR7/8 agonist can boost antibody titers to pneumococcal conjugate vaccine at birth [66].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Trehalose 6,6ʹ-dibehenate (TDB) is a synthetic analog of mycobacterially-expressed trehalose-6,6-dimycolate (TDM) that targets the PAMP receptor, MINCLE (macrophage inducible Ca 2+ -dependent lectin receptor). TDB was shown to activate human newborn DCs and enhanced Th1 polarizing cytokine production by DCs when given in combination with a TLR7/8-ligand [116]. TDB enhanced protection against influenza in immunized neonatal mice through the induction of Tfh cells and highaffinity plasma cells [110].…”
Section: Benefits Of Sugar-based Adjuvants In Neonatal Vaccinesmentioning
confidence: 99%